Microbial and Physicochemical Dynamics of Kocho, Fermented Food from Enset - Seboka, Dereba Workineh; Bejiga, Abay Tabor; Turunesh, Debela Jufar; Turito, Andualem Arimo; Girma, Abayeneh (International Journal of Microbiology, 2023)
Over 20 million Ethiopians depend on enset (Ensete ventricosum) as a staple or costaple food. “Kocho,” “Bulla,” and “Amicho” are the three main food types obtained from enset. This review aimed to summarize the physicochemical and microbial dynamics of kocho. It is the most common food obtained from the scraped pseudostem and decorticated corm of enset after a long period of fermentation. The quality of kocho depends on the maturity of the enset plant, the enset processing method, the fermentation period, and the dynamics of microorganisms during the fermentation process. Microorganisms play a significant role in kocho fermentation to enhance its nutritional quality, improve sensory properties, and reduce spoilage and disease-causing agents. The populations of microbes available in kocho fermentation include lactic acid bacteria (LAB), Enterobacteriaceae, acetic acid bacteria (AAB), yeasts and molds, and Clostridium spp., which have both positive and negative impacts on kocho quality. There is a visible variation in microbial dynamics during kocho fermentation caused by the fermentation period. As the fermentation day increases, species of LAB also increase, whereas counts of Enterobacteriaceae decrease. This is due to a decrease in pH, which leads to an increase in titratable acidity. Moisture content also slightly decreases as fermentation progresses. Dynamics in the microbial population and physicochemical parameters ensure the development of desirable qualities in kocho and enhance the acceptability of the final product. Organic acids (such as lactic acid, acetic acid, and propionic acid), bacteriocins, phenolic compounds, flavonoids, and tannins are bioactive compounds produced by microorganisms during Kocho fermentation. Further research is needed on the molecular identification of microorganisms during Kocho fermentation.